Aspiring Geopark Gorontalo: Solusi Persiapan Situs Geologi Untuk Pariwisata Pasca-COVID-19 - Meilinda Lestari Modjo; Krishna Anugrah; Yayu Indriati Arifin (Jurnal Penelitian Pendidikan IPA, 2024)
The Geosite Area of Gorontalo Evaluated Using Quantitative Descriptive Research Method for Tourism Preparedness Post-COVID-19" The Gorontalo geosite area was evaluated using a quantitative descriptive research method in this study to determine its readiness to host tourism after COVID-19. Changes in the attitudes and behaviours of tourists have occurred as a result of the COVID-19 epidemic, significantly impacting the domestic and international tourism environment. The objective of this research is to gain an understanding of the factors motivating tourists, classify various forms of tourism, and observe specific geosites in Gorontalo based on official designations. Different local attitudes towards the "new normal tourism" are crucial factors in the highlighted destination preparation differences presented in the conclusions. Despite the economic considerations influencing the continuous implementation of health protocols, the government, local communities, and businesses must collaborate towards achieving optimal and sustainable tourism recovery